2015
DOI: 10.1080/15459624.2015.1009982
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Process on Quantity and Composition of Laboratory-generated Bitumen Emissions

Abstract: In this study we investigated the impact of temperature on emissions as related to various bitumen applications and processes used in commercial products. Bitumen emissions are very complex and can be influenced in quantity and composition by differences in crude source, refining processes, application temperature, and work practices. This study provided a controlled laboratory environment to study five bitumen test materials from three European refineries; three paving grade, one used for primarily roofing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…This study observed that, the high concentration of HC at the Oven heating/Crude Oil Boiling and Vapour Condensation Units of the refineries might be as a result of direct combustion of residual crude oil and dry wood as a source of energy for the distillation process. Also, the direct application of heat to the crude oil-bearing oven results in high level evaporation of lighter fractions of the crude oil ( Bolliet et al., 2015 ; Yan et al., 2017 ; Gurjap et al., 2019 ). While its high concentration at the Refined Products Collection/Storage Unit as observed, might be due to large quantity storage of refined petroleum products collected in receiving facilities accompanied with the high volatile tendency of refined products as heat is given off for temperature reduction ( API, 1991 ; 1997 ; Taylor and Francis, 2012 ; Weli and Itam, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study observed that, the high concentration of HC at the Oven heating/Crude Oil Boiling and Vapour Condensation Units of the refineries might be as a result of direct combustion of residual crude oil and dry wood as a source of energy for the distillation process. Also, the direct application of heat to the crude oil-bearing oven results in high level evaporation of lighter fractions of the crude oil ( Bolliet et al., 2015 ; Yan et al., 2017 ; Gurjap et al., 2019 ). While its high concentration at the Refined Products Collection/Storage Unit as observed, might be due to large quantity storage of refined petroleum products collected in receiving facilities accompanied with the high volatile tendency of refined products as heat is given off for temperature reduction ( API, 1991 ; 1997 ; Taylor and Francis, 2012 ; Weli and Itam, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…This trend in the emissions might result from the intensified heat supplied to the boiler with regular input of residual crude to the refining fire to maintain high temperature for larger oven sizes/processing capacities, as the frequency of fire intensification is dependent on the oven size/processing capacity. Also, increased oven size acquires increase surface area which encourages high evaporation ( McJannet et al., 2008 : Bolliet et al., 2015 ; Prasanna et al., 2015 ; Lehman, 2016 ).
Figure 6 Emissions from oven heating/crude oil boiling unit.
…”
Section: Resultsmentioning
confidence: 99%
“…In the laboratory, this includes sampling through the use of filters to concentrate emissions, headspace sampling, headspace solidphase microextraction sampling, and nonseparative real-time sampling. 29 Many current laboratory methods used to examine bitumen emissions rely on the extraction and concentration of emissions onto filters. When using this method, bitumen is heated and mixed in a closed vessel, while air is pulled through the vessel's headspace and subsequently through filters to collect and concentrate the emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Many current laboratory methods used to examine bitumen emissions rely on the extraction and concentration of emissions onto filters. When using this method, bitumen is heated and mixed in a closed vessel, while air is pulled through the vessel’s headspace and subsequently through filters to collect and concentrate the emissions. ,, This method has expanded significantly upon the understanding of bitumen fumes and has been essential in establishing health advice for persons that are regularly exposed to bitumen emissions. …”
Section: Introductionmentioning
confidence: 99%
“…The introduction of polymer modifiers makes the internal structure of the asphalt binder become more compact. The asphalt molecules, especially the light components, are fixed in the network structure through the formation of reticular structure, thereby reducing the emission of asphalt VOCs [ 8 ]. The second one is adsorbents, which are regarded as one of the mainstream techniques due to their low energy consumption, facile operation of adsorption processes, and low operation cost [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%